Comparison of outcomes between neoadjuvant chemoradiotherapy and neoadjuvant chemotherapy in patients with locally advanced esophageal cancer: A network meta-analysis. (December 2021) - Fan, Ningbo; Wang, Zhefang; Zhou, Chenghui; Bludau, Marc; Contino, Gianmarco; Zhao, Yue; Bruns, Christiane
Abstract: Background: Neoadjuvant chemoradiotherapy (NCRT) or neoadjuvant chemotherapy (NCT) followed by surgery are two standard strategies in treating locally advanced esophageal cancer (EC). We aim to compare NCRT and NCT in the management of locally advanced EC patients. Methods: MEDLINE, Embase, CENTRAL, and conferences were systematically searched for clinical trials published up to September 2021. Pairwise comparisons and Bayesian network meta-analyses were conducted to compare overall survival (OS) and disease-free survival (DFS) by reporting the hazard ratio (HR) and 95% credible intervals (CrIs). The study was registered at PROSPERO (CRD42020170619). Findings: 25 trials with 4563 EC patients met inclusion criteria. NCRT improved OS (HR: 0·72, 95%CrI: 0·63–0·82) and DFS (HR: 0·72, 95%CrI: 0·63–0·81) compared to surgery alone. NCRT improved OS (HR: 0·83, 95%CrI: 0·69–0·99) and DFS (HR: 0·83, 95%CI: 0·69–0·99) compared to NCT. Subgroup analysis demonstrated that both NCRT (HR: 0·77, 95%CrI: 0·65–0·90) and NCT (HR: 0·81, 95%CrI: 0·67–0·99) improved OS than surgery in esophageal squamous cell carcinoma (ESCC) patients. No significant differences were observed between NCRT and NCT regarding OS (HR: 0·95, 95%CrI: 0·75–1·19) and DFS (HR: 0·90, 95%CrI: 0·50–1·62) in ESCC. The short-term outcomes were similar between NCRT and NCT. The three treatment strategies were comparable in esophageal adenocarcinoma (EAC) subpopulations. Interpretation: The study corroborated current guidelines in addressing the importance of analysing EC according to histopathological types. The analysis suggested that in locally advanced ESCC patients, both NCRT and NCT improved OS as compared to surgery alone, whereas no clear evidence supported the optimal strategies between NCRT and NCT. More RCTs comparing different therapeutic strategies in EAC patients are warranted. Funding: Köln Fortune Program, University of Cologne.